PEMBERDAYAAN DAN KOMERSIALISASI PRODUK UNGGULAN DESA MELALUI METODE ARTIFICIAL INTELLIGENCE (AI) & INFLUENCER MARKETING BERBASIS TEKNOLOGI MODERN PADA KELOMPOK TANI DAN UMKM DI KECAMATAN SIDAMANIK - Liang, William; Sirait, Sarida (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
The biggest problem that is always faced by farmer groups and MSMEs is the Commercialization and Utilization of technology which is very minimal in the downstream process of superior products. This is because farmers and MSME actors in the village are still very far from modern technology and business strategies. Farmers and MSME actors are only able to plant superior products such as coffee and produce downstream products using traditional methods. Their inability to commercialize their products forces them to sell their products to producers or middlemen at low prices, as a result the profits they obtain are very low from what is expected. The results of an initial survey conducted by researchers in the Farmer Group and MSMEs found that agricultural products and processed MSMEs from this District were very good and worth selling, but the limited use of technology in the management and marketing management made the downstream productivity of these coffee farmers low. MSME products from Sidamanik District are very numerous and diverse, for example processed cassava, corn, ginger, tea leaves, and coffee which are produced into packaged foods but with very minimal use of technology. To overcome this problem, researchers will create and Artificial Intelligence (AI) & Influencer Marketing methods based on Modern Technology where products will be marketed online and offline through information systems or applications specifically designed for product marketing. In addition, researchers will also use the Artificial Intelligence (AI) method in creating marketing engineering based on modern technology. The purpose of this study is to implement the Empowerment and Commercialization of Superior Village Products Through the Artificial Intelligence (AI) & Influencer Marketing Method Based on Modern Technology. If this is implemented, the productivity of farmers and MSMEs will increase because products can be marketed across provinces with the Artificial Intelligence (AI) & Influencer Marketing method.